Geochemical and mineralogical characteristics of andesitic derived laterite from the Serian Volcanic, West Sarawak, Malaysia: potential for ion-adsorption-type ree deposit - Ledyhernando Taniou,; Mohd Basril Iswadi Basori,; Sanematsu, Kenzo, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The rare earth elements (REEs) found in the Earth’s crust are highly sophisticated minerals that have a significant application in various high-tech industries such as green technology and defense. Due to the limited study of REE derived from volcanic rocks, the main objectives of this research are focusing to determine the geochemical and mineralogical, as well to examine the potential resources of ion-adsorption type deposits in volcanic rock and their derived laterite profile from the Serian Volcanic, West Sarawak, Malaysia. Two lateritic profiles were examined, and the parent volcanic rock is classified as basaltic trachyandesite in composition with moderate REE content of 209 ppm. In both profiles the abundance of the REE is subjected to the deep weathering through CIA (99-100%) that promote the enrichment of REE to the laterite profile up to 1715.98 ppm. The dominance of kaolinite mineral as an absorbent material, coupled with the absence of RE mineral in the laterite samples, indicates the potential for ion-adsorption clay deposit with high (>75%) extracted REY content, as determined by ion-exchangeable analysis. The chondrite-normalized REE pattern for both profiles were almost flat for parent rock, whereas LREE and HREE were equally abundant in the laterite profile. However, the TREE significantly decrease toward the upper part of each profile. This study also demonstrates that laterites with a high TREE and low Ce anomalies have the highest ion-exchangeable (REY) fraction relative to the parent rock content, suggesting that ion-adsorption deposit in this region have the potential to recover REY in terms of resources quantity.